The Effectiveness of Implementing the Project Based Learning Model in Teaching the Writing Element of Procedural Texts Based on the Local Wisdom of Sengkang Silk Sarong Among Eleventh-Grade Students of Vocation High School - Nurmilasari; Muh. Safar; Andi Tenri Sua; Ilma Rahim (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
The Effectiveness of Applying the Project Based Learning Model in Teaching the Writing Elements of Procedural Texts Based on the Local Wisdom of Sengkang Silk Sarongs among Eleventh Grade Students of SMK Negeri 1 Wajo. This study aims to determine the effectiveness of the Project Based Learning (PjBL) model in teaching the writing elements of procedural texts based on the local wisdom of Sengkang silk sarongs among eleventh-grade students of SMK Negeri 1 Wajo. This research employed a quantitative approach with a pre-experimental design (one-group pretest-posttest design). The subjects were 32 students of the Computer and Network Engineering Department (TKJ) selected through purposive sampling. Research instruments included observation sheets for teacher and student activities and a writing skills test for procedural texts. Data were analyzed using descriptive statistics and t-tests to examine the difference between pretest and posttest results. The findings revealed a significant improvement in students’ ability to write procedural texts after the implementation of the PjBL model based on the local wisdom of Sengkang silk weaving. The posttest scores were higher than the pretest scores, indicating that the PjBL model effectively enhanced students’ writing skills. Moreover, this model fostered active participation, creativity, and cultural awareness among students. Integrating local wisdom into the learning process provided more meaningful and contextual learning experiences while contributing to the preservation of regional cultural values.